The physical and dynamical characteristics of the asteroid 4940 Polenov - Vchkova-Bebekovska, E.; Todorovic, N.; Kostov, A.; Donchev, Z.; Borisov, G.; Apostolovska, G. (National Library of Serbia, 2021)
The asteroid (1986 QY4) 4940 Polenov is the first Solar system object whose 3D shape is determined using the observations from the newly built Astronomical Station Vidojevica (ASV). Here we present the results of photometric observations for Polenov, gathered from the ASV, and from the Bulgarian National Astronomical Observatory (BNAO) Rozhen, during 2014, 2019 and 2020 apparitions. Polenov is a 17.8km object located in the outer part of the main belt and belongs to the asteroid family Themis. We have determined the lightcurves, the synodic period of 4.161?0.001 h, as well as the solution for the shape and spin axis. Using the lightcurve inversion method, the combination of our lightcurves and the sparse data from ATLAS{HKO and ATLAS-MLO, we also found the sidereal period, indicating a retrograde rotation of the asteroid, with two possible mirrored pole solutions. The ratio of the largest to smallest reecting surface is about 1.4. In addition, we studied the dynamical properties of the asteroid and obtained a long stability time that exceeds 0.4 Gyrs.